JUSTIFICATION OF LOGISTIC CONTROL SYSTEMS OF AN ENTERPRISE BASED ON ABC and XYZ ANALYSIS - Razumova, Kateryna; Temchenko, Oleksandr; Shevchuk, Nataliia; Maksymova, Olena (Science-based technologies, 2021)
In the process of managing industrial enterprise the main point of attention is the process of analysis and controlling the costs of the logistics and main activities in general, and separately by types, goals and deadlines. Expenses are the monetary expression of the sums of factors, that are necessary for the successful implementation of the enterprise by its purchasing, sales and transport and logistics activities based on an effective cost management system. The use of combined ABC and XYZ - analyzes allows to increase the efficiency of the commodity resources management system, increase the share of highly profitable products without violating the principles of assortment policy, identify key products and the reasons that affect its quantity stored in the warehouse. It is proved that the cost of production of marketable products is one of the most important in managing the economic parameters enterprises, as this indicator reflects the growth of labor productivity, resource savings, technical progress, efficiency of logistics management systems. Based on the results of ABC and XYZ analysis, the most significant activities of the metallurgical enterprise PJSC "ArcelorMittal Kryvyi Rih" are identified, which increase the efficiency of organizational, technical-technological and managerial decisions due to their target orientation, highlight the most important, appropriate costs and their management for 2020, and also allows to forecast indicators of components of operating expenses for 2021 and 2022. It is proved that the management of total costs in the logistics system is a leading parameter for optimizing production, including transport and warehousing costs, as well as financial costs of the enterprise. Careful control over the current costs of the company will allow the results of several operating periods to develop the most efficient logistics systems and, accordingly, an effective cost management methodology for PJSC "ArcelorMittal Kryvyi Rih" in the nearest future